New Advertising Agency Roles in the Ever-Expanding Media Landscape. Issue 3 (2nd September 2018) - Windels, Kasey; Stuhlfaut, Mark
Abstract: As advertising shifted from traditional to digital media spaces, advertising agencies quickly developed digital advertising expertise. Through interviews with 34 practitioners, this study examines the new roles and positions adopted by advertising agencies to accommodate digital media. Due to the complexity of the digital advertising space, four broad categories of new roles emerged from the data related to account management, strategy, creative, and production. This research is the first to identify and describe the roles in positions such as creative technologist, user experience strategist, and project manager. The new roles signify a fundamental shift in the industry from framing technology in terms of its production value, to framing technology in terms of its strategic value.